Percutaneous transluminal coronary angioplasty in Nepalese diabetic patients: Do they carry extra risk to revascularization process? - Khatun, F; Rawat, B; Vaidya, A; Rajbhandari, S; Bhatta, Y (Journal of Kathmandu Medical College, 2012)
Background and Objectives: There is evidence that diabetes carries risk of various complications and adverse outcome with coronary revascularisation procedures. The aim of this study was to analyze the outcomes and complications of Percutaneous Transluminal Coronary Angioplasty in Nepalese diabetic patients compared to non-diabetic patients. Method: A hospital-based comparative cross-sectional study was conducted at Norvic International Hospital, Kathmandu, Nepal. A total of 702 consecutive Percutaneous Transluminal Coronary Angioplasty patients coming to the hospital from 2002 to 2010 were included. Angioplasty was performed using radial and femoral routes in a standard setting with standard techniques. Information on other background risk factors was recorded. Success of the procedures and presence of major and minor complications were observed. Results: Of the 702 patients participating in this study, 259 were diabetic and 443 were non-diabetic. Success rates were similar: 256 (98.8%) of diabetic and 438 (98.8%) of non-diabetic had a successful Percutaneous Transluminal Coronary Angioplasty. Complications of the procedure were however higher in the diabetic patients with higher in-hospital death (odds ratio 3.4, 95% confidence Interval: 0.6-19.1), compared to non-diabetic patients. Conclusion: The overall outcome of Percutaneous Transluminal Coronary Angioplasty was equally successful in diabetic and non-diabetic populations groups. But the complications were higher with the diabetic group which were because of presence of other co-morbidities in this group and were not procedure-related. DOI: http://dx.doi.org/10.3126/jkmc.v1i1.7250 Journal of Kathmandu Medical College, Vol. 1, No. 1, Issue 1, Jul.-Sep., 2012 pp.16-20